2015
DOI: 10.1007/s11248-015-9880-x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic plants over-expressing insect-specific microRNA acquire insecticidal activity against Helicoverpa armigera: an alternative to Bt-toxin technology

Abstract: The success of Bt transgenics in controlling predation of crops has been tempered by sporadic emergence of resistance in targeted insect larvae. Such emerging threats have prompted the search for novel insecticidal molecules that are specific and could be expressed through plants. We have resorted to small RNA-based technology for an investigative search and focused our attention to an insect-specific miRNA that interferes with the insect molting process resulting in the death of the larvae. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…The larvae of cotton bollworm, Helicoverpa armigera, that fed on bacteria expressing an artificial miRNA (amiRNA) sequence specifically targeting the ecdysone receptor (EcR) gene showed greater mortality, developmental defects, and a significant decline in reproductive ability (Yogindran and Rajam, 2016). Feeding on transgenic tobacco plants producing an amiRNA based on endogenous miR-24 against a chitinase gene significantly reduced the level of chitinase transcripts in H. armigera larvae, causing cessation of molt (Agrawal et al, 2015). Although RSB larvae that were continuously fed with transgenic Csu-novel-miR-15 rice showed a 4-day delay of pupation, no significant lethal effect was observed (Jiang et al, 2016), the target genes and biological function of this novel miRNA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The larvae of cotton bollworm, Helicoverpa armigera, that fed on bacteria expressing an artificial miRNA (amiRNA) sequence specifically targeting the ecdysone receptor (EcR) gene showed greater mortality, developmental defects, and a significant decline in reproductive ability (Yogindran and Rajam, 2016). Feeding on transgenic tobacco plants producing an amiRNA based on endogenous miR-24 against a chitinase gene significantly reduced the level of chitinase transcripts in H. armigera larvae, causing cessation of molt (Agrawal et al, 2015). Although RSB larvae that were continuously fed with transgenic Csu-novel-miR-15 rice showed a 4-day delay of pupation, no significant lethal effect was observed (Jiang et al, 2016), the target genes and biological function of this novel miRNA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Agrawal et al. () recently reported cessation of H. armigera larval molting after feeding on transgenic tobacco engineered to express a miRNA targeting the H. armigera group I chitinase hachi . Future studies in L. hesperus will focus on using RNAi‐based methods to elucidate the roles of the 10 chitinase‐like sequences in molting and determining their potential usefulness in controlling populations of this pest species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Arabidopsis expressing two amiRNAs targeting the mRNA of the P69 and HC-Pro proteins showed resistance to Turnip yellow mosaic virus and Turnip mosaic virus, respectively (Niu et al, 2006). Agrawal et al (2015) showed that tobacco overexpressing an engineered amiRNA was resistant to Helicoverpa armigera.…”
Section: Artificial Mir Genesmentioning
confidence: 99%
“…Greater target specificity can be achieved with overexpression driven by tissue‐specific (Niu et al ., ) or stress‐inducible (Gao et al ., ) promoters. Additional strategies include the overexpression of target mRNAs that are resistant to specific miRNAs (Guan et al ., ), the expression of artificial target mimics that can cancel out the effect of endogenous miRNA activity (Sharma et al ., ) and the expression of artificial MIR gene targeting only the desired mRNAs (Agrawal et al ., ). Jian et al .…”
Section: The Role Of Mirna In Plant Abiotic or Biotic Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation